Faktor pembelajaran kewirausahaan dan motivasi berwirausaha dalam meningkatkan niat berwirausaha - Hafizhah, Khansa; Mulyadi, Hari; Utama, R Dian H (Journal of Business Management Education (JBME), 2019)
Abstract: The main goals of this study is to derive the positive effect of entrepreneurial learning on entrepreneurial intentions, the effect of entrepreneurial motivation on entrepreneurial intentions, and the combined influence of entrepreneurial learning and entrepreneurial motivation on entrepreneurial intentions.  This study has been performed using a group of students from the Bandung City Vocational egvtechnique used was a questionnaire with a sample size of 107 respondents.  The results of this study found that the influence of entrepreneurial learning on entrepreneurial intentions belonged to the strong category, motivational motivation influenced the intention of entrepreneurship included in the strong category, and entrepreneurial learning and entrepreneurial motivation influenced the intention of entrepreneurship, including in the strong category.  (In this study it is found, if the picture of entrepreneurial learning was effective, it would increase the intention of student entrepreneurship.)  The high motivation of student entrepreneurship will create a high intention of entrepreneurship.  In addition, if entrepreneurial learning is effective and coupled with a high motivation for entrepreneurship, the intention of student entrepreneurship will increase.